Reconsidering the Proposal of Increasing Political Party Funding Assistance and Its Correlation with Quality of Democracy - Arif Zainudin (JURNAL AKTA, 2026)
In the period prior to Indonesia’s general elections, the discourse on increasing public funding for political parties has gained prominence. Minister of Home Affairs Tito Karnavian proposed tripling party subsidies from Rp1,000 to Rp3,000 per valid vote, arguing that higher state funding would enhance party financial independence, reduce dependency on private donors, and improve democratic quality. However, this proposal remains controversial given that party financial reporting has not met transparency and accountability principles, and sanctions for violations remain unenforced. This study examines whether increased APBN (State Budget) funding for political parties contributes to improving democratic quality in Indonesia. Using normative legal research methodology combined with empirical analysis of BPK audit reports and party financial data, this research analyzes the regulatory framework governing party financing under Government Regulation No. 1 of 2018, actual utilization patterns of state assistance, and the correlation between funding levels and democratic performance indicators. The findings reveal a critical paradox: while APBN funding theoretically aims to reduce oligarchic influences and strengthen democratic institutions through enhanced political education, actual implementation demonstrates significant gaps between normative expectations and empirical realities. The absence of sanctions for non-compliance with political education mandates, coupled with parties’ prioritization of operational expenses over educational responsibilities, undermines policy objectives. Furthermore, the minimal APBN allocation (0.0007% in 2010) remains insufficient to replace illicit funding sources or meaningfully support comprehensive political education programs. The study concludes that increased funding alone cannot improve democratic quality without robust enforcement mechanisms, binding allocation guidelines (75% for political education, 25% for operations), and stringent accountability frameworks audited by independent bodies. These findings provide objective references for reformulating political party financing policies and contribute significantly to electoral law discourse in Indonesia.